A 24‐generation‐old founder mutation impairs splicing of RBBP8 in Pakistani families affected with Jawad syndrome. Issue 4 (16th July 2021) - Kaygusuz, Emrah; Khayyat, Arwa Ishaq A.; Abdullah, Uzma; Budde, Birgit Susanne; Asif, Maria; Ahmed, Ilyas; Makhdoom, Ehtisham Ul Haq; Sur‐Erdem, Ilknur; Baig, Jamshaid Mahmood; Khan, Muhammad Mohsin Ali; Toliat, Mohammad Reza; Becker, Christian; et al.
Abstract : Jawad syndrome is a multiple congenital anomaly and intellectual disability syndrome with mutation in RBBP8 reported only in two families. Here, we report on two new families from Pakistan and identified a previously reported variant in RBBP8, NM_002894.3:c.1808‐1809delTA. We could show that this mutation impairs splicing resulting in two different abnormal transcripts. Finally, we could verify a shared haplotype among all four families and estimate the founder event to have occurred some 24 generations ago.